PROSEDUR PENANGANAN PERMASALAHAN OPERASIONAL STAN PESERTA PAMERAN INDONESIA INTERNATIONAL WEDDING FESTIVAL 2017 - Kautsar, Fachri Muhammad; Setiawati, Rahmi (Journal of Indonesian Tourism and Policy Studies, 2018)
Indonesia International Wedding Festival 2017 is the largest wedding and honeymoon exhibition at the beginning of the year held by Weddingku and Radyatama. Each operation certainly does not escape from the problem, especially in operational aspect. Therefore, the organizer has its own procedures in operational operations. This paper will discuss the operational issues of special hall procedures being undertaken by participants in the operation of their booth. This discussion is required to know anything. The method used in the manufacture and writing of this Final Project Task is a descriptive method through the written or oral words of the people and the behavior observed. I also use observation method that is work practice that exist in PT Dyandra Promosindo. I found the most common issue is marking and electric power. Handling is done to identify the problem and after found the source, direct advance more than ten minutes.